Determination of Pyrethroids in Tea Brew by GC-MS Combined with SPME with Multiwalled Carbon Nanotube Coated Fiber - Dongxia Ren; Chengjun Sun; Guanqun Ma; Danni Yang; Chen Zhou; Jiayu Xie; Yongxin Li (International Journal of Analytical Chemistry)
A new method has been developed to simultaneously determine 7 pyrethroid residues in tea brew using gas chromatography-mass spectrometry (GC-MS) combined with solid phase microextraction (SPME) with multiwalled carbon nanotubes (MWCNTs) coated fiber. The MWCNTs coated fiber of SPME was homemade by using stainless steel wire as coating carrier and polyacrylonitrile (PAN) solution as adhesive glue. Under the optimized conditions, a good linearity was shown for bifenthrin, fenpropathrin, permethrin, and cyfluthrin in 1–50 ng mL−1 and for cypermethrin, fenvalerate, and deltamethrin in 5–50 ng mL−1. The correlation coefficients were in the range of 0.9948–0.9999. The average recoveries of 7 pyrethroids were 94.2%–107.3% and the relative standard deviations (RSDs) were less than 15%. The detection limit of the method ranged from 0.12 to 1.65 ng mL−1. The tea brew samples made from some commercial tea samples were analyzed. Among them, bifenthrin, fenpropathrin, and permethrin were found. The results show that the method is rapid and sensitive and requires low organic reagent consumption, which can be well used for the detection of the pyrethroids in tea brew.